SHIFTING INTERPRETATION OF JOHN KERRY’S SPEECH ABOUT SYRIA CONFLICT REPORTED BY KOMPAS TV - Dewi, Sheellviana; Himmawati, Dian Rivia (Paramasastra, 2017)
The issue of John Kerry?s speech about Syria conflict reported by Kompas TV takes interpretation process. Interpretation used in transforming source language (John Kerry/English) to target language (Kompas TV/Indonesian). The aim of this study is revealing shifting interpretation inserted by Kompas TV while reporting John Kerry?s speech about Syria conflict. Documentary video from Kompas TV and the United States official channel on YouTube is the data which consist of three videos. Qualitative data approach is applied to this study because the analysis gives explanation to strength the findings. The result of the analysis shows that Kompas TV used complex syntax, making long passage into a sentence, de-verbalization, and compression to get John Kerry?s idea. All of John Kerry?s utterances are simplified into the simple one. Hence, Kompas TV shifts the interpretation through complex syntax process which  is inserted in semantic macrostructures, syntactic of subject position, self-define of terrorist, and disclaimer to reject racism.